Effect of transcranial direct current stimulation (tDCS) over the prefrontal cortex combined with cognitive training for treating schizophrenia: a sham-controlled randomized clinical trial - Pedro Shiozawa; July Silveira Gomes; Daniella Valverde Ducos; Henrique Teruo Akiba; Álvaro Machado Dias; Alisson Paulino Trevizol; Ricardo R. Uchida; Natasza Orlov; Quirino Cordeiro (Trends in Psychiatry and Psychotherapy)
Abstract Introduction: We report a transcranial direct current stimulation (tDCS) protocol over the dorsolateral prefrontal cortex (DLPFC) combined with cognitive training in schizophrenia. Method: We assessed psychotic symptoms in nine patients using the Positive and Negative Syndrome Scale (PANSS). All evaluations were scored at baseline, at the end of the intervention protocol, and during a 4-week follow-up. The tDCS protocol consisted of 10 consecutive sessions over 5-day periods. We placed the cathode over the right and the anode over the left DLPFC. For sham stimulation, we turned the device off after 60 seconds. Cognitive training consisted of the administration of N-back and sequence learning tasks. Results: We performed an analysis of covariance (ANCOVA) to adjust for the dependent variable PANSS, considering the interaction with baseline severity scores (p = 0.619). Mixed analysis of variance (ANOVA) showed no statistical significance between the groups regarding final PANSS scores. Conclusion: The results failed to demonstrate that the concomitant use of tDCS and cognitive training is effective to improve clinical outcomes in patients with schizophrenia. The present findings should be analyzed with care, considering the small sample size. Larger controlled trials on electric/cognitive stimulation should be produced in order to enhance therapeutic strategies in schizophrenia.